2016
DOI: 10.1074/jbc.m115.710277
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Monocarboxylic Acid Transporter 1 Trafficking by the Canonical Wnt/β-Catenin Pathway in Rat Brain Endothelial Cells Requires Cross-talk with Notch Signaling

Abstract: The transport of monocarboxylate fuels such as lactate, pyruvate, and ketone bodies across brain endothelial cells is mediated by monocarboxylic acid transporter 1 (MCT1). Although the canonical Wnt/␤-catenin pathway is required for rodent blood-brain barrier development and for the expression of associated nutrient transporters, the role of this pathway in the regulation of brain endothelial MCT1 is unknown. Here we report expression of nine members of the frizzled receptor family by the RBE4 rat brain endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 72 publications
(60 reference statements)
0
15
0
Order By: Relevance
“…Studies have shown that cell cycle control genes and Wnt signaling are upregulated in BMs (19). In endothelial cells from rat brains, the Wnt/β-catenin pathway interacts with the Notch pathway to increase the amount of monocarboxylic acid transporter 1 (MCT1) protein (20). MCT1 promotes pyruvate export and cell proliferation and is upregulated in glycolytic cancer cells, therefore MCT1 inhibitors block proliferation and may be useful cancer therapeutics (21).…”
Section: Signaling Pathways and Metabolismmentioning
confidence: 99%
“…Studies have shown that cell cycle control genes and Wnt signaling are upregulated in BMs (19). In endothelial cells from rat brains, the Wnt/β-catenin pathway interacts with the Notch pathway to increase the amount of monocarboxylic acid transporter 1 (MCT1) protein (20). MCT1 promotes pyruvate export and cell proliferation and is upregulated in glycolytic cancer cells, therefore MCT1 inhibitors block proliferation and may be useful cancer therapeutics (21).…”
Section: Signaling Pathways and Metabolismmentioning
confidence: 99%
“…Our investigation of OATs in cultured cells and in rat kidney slices demonstrated that the PKC‐induced acceleration of OAT internalization is due to an elevation in OAT ubiquitination . Ubiquitination‐mediated functional regulation has been observed with other members of solute carrier family of drug transporters . Mass spectroscopy analysis revealed that the ubiquitination of OAT occurs through the conjugation of a lysine 48‐linked polyubiquitin chain to the transporter .…”
Section: Regulation Of Oat By Ubiquitinationmentioning
confidence: 79%
“…This effect was likely caused, at least in part, by an upregulated PI3K/AKT pathway, Wnt/β-catenin signaling, and Notch1 signaling. Although not discussed in this research, crosstalk between these three pathways is also a pivotal factor for the fate of NSCs 52 . Our data provide novel insight into the molecular mechanisms of rEWST on NSCs and important preclinical references supporting the basis for further development of neurological function recovery promoted by NSCs recruitment.…”
Section: Discussionmentioning
confidence: 93%